Profil Usaha Mie Ba Garuda Asli Di Maumbi Kecamatan Kalawat Kabupaten Minahasa Utara - Wawolangi, Natalia Enjellina; Rumagit, Grace Adonia Josephine; Ngangi, Charles Reijnaldo (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The purpose of this research is to describe the Business Profile of Mie Ba Garuda Original Maumbi, Kalawat District, North Minahasa Regency. Identify the history contained in the Mie Ba Garuda Asli restaurant. Identify what raw materials are used in the process of making Original Ba Garuda Noodles. Analyzing the profit of selling the number of ba meat noodle products produced by Mie Ba Garuda Asli. The results showed that the original ba garuda noodle business was opened in 1965 by Mr. Endi Lucas and was located on Jalan Garuda. This Mie Ba Garuda Asli restaurant is open every Monday - Saturday from 08.00 - 22.00. The amount of noodle raw materials used ranges from 257-260 kg and the pork used ranges from 58-60 kg per month. Every day is the highest demand and at the highest demand, the profit earned is IDR 36,960,000 per month.